(untitled) (Revista Contexto & Educação, 2025)
We present the results of a review study that sought to investigate the profile of research on assessment, within the scope of Science Education, in the theses and dissertations contained in the Catalog of Theses & Dissertations, available on the CAPES website, from 2013 to 2022. To this end, a bibliographical research of the state of knowledge type was carried out, having as a methodological reference the documentary analysis of the synthesis type. In conducting this analysis, we used as a theoretical reference the concepts of Formative Assessment, Examination and Emancipatory Assessment. We observed that the majority of the 79 studies analyzed were carried out at the basic education level, with the presence of these studies in graduate studies being insignificant. The studies analyzed mostly address issues related to the methodological and operational aspects of assessment, with little space for sociopolitical questions and low criticality. The concept of Formative Assessment is adopted by most of the studies analyzed, the logic of the Exam is present in a significant amount of research, while the emancipatory perspective is assumed by a reduced number of works. Thus, there are indications of the need to expand and deepen research in Science Education, with regard to the theme of assessment, with decoloniality being a theme still unexplored, and there is a demand for future research.